Penerapan Program Tahfidzul Qur’an di SMP Islamic Center Samarinda - Dianto, Alpin; Sultan, Lucky Purnama; Hidayah, Miftahul; Sudadi, Sudadi (Borneo Journal of Islamic Education, 2023)
Abstract This study aims to determine the implementation of the tahfidzul qur'an program at Islamic Center Middle Schools, a flagship program in their curriculum with the aim of making students with Qur'anic souls in the future. Qualitative descriptive method used in this study. with the application of the tahfidzul qur'an program as the focus of this research. conducting observations, interviews and documentation as data collection techniques. Data analysis used was data collection, data reduction, data presentation and drawing conclusions, as well as triangulation of sources and techniques used in data validity. The results of this study stated that the planning of the tahfidzul qur'an program at the Samarinda Islamic Center Middle School was in accordance with the stages of the tahfidzul qur'an program, starting from the objectives, materials, methods and assessment. the implementation is also going well by using the read-see method between students and teachers and between students so that students' memorization of the Koran is continuously maintained. As well as evaluating the tahfidzul qur'an program which is carried out by depositing student memorization with the teacher in order to evaluate students' fluency which is carried out daily or once every 3 months according to the assessment standards in student report cards. Keyword: Tahfidz, Al-Qur’an, PAI Abstrak Penelitian ini memiliki tujuan untuk mengetahui penerapan program tahfidzul qur’an di SMP Islamic Center yang menjadi program unggulan dalam kurikulum mereka dengan tujuan menjadikan siswa berjiwa Qur’ani di masa mendatang. Metode deskriptif kualitatif digunakan dalam penelitian ini. dengan penerapan program tahfidzul qur’an sebagai fokus peneltian ini. melakukan observasi, wawancara dan dokumentasi sebagai teknik pengumpulan data. Analisis data yang digunakan adalah pengumpulan data, reduksi data, penyajian data dan penarikan simpulan, serta triangulasi sumber dan teknik digunakan dalam keabsahan data. Hasil penelitian ini menyatakan bahwa perencanaan program tahfidzul qur’an di SMP Islamic Center Samarinda sudah sesuai dengan tahapan-tahapan program tahfidzul qur’an, mulai dari tujuan, materi, metode serta penilaiannya. pelaksanaannya pun berjalan dengan baik dengan menggunakan metode baca simak antara siswa dan guru maupun antar siswa agar hafalan al-qur’an siswa terus menerus tetap tertajaga. Serta evaluasi program tahfidzul qur’an yang dilakukan dengan menyetorkan hafalan siswa kepada guru guna mengevaluasi kelancaran siswa yang dilakukan harian maupun setiap 3 bulan sekali sesuai standar penilaian di rapor siswa. Kata kunci:Tahfidz, Al-Qur’an, PAI